(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
The Relationship between the Role of Farmer Groups and Increased Productivity of Cocoa Merta Abadi Farmer Group (Case in Ekasari Village, Melaya District, Jembrana Regency). One of the institutions developed to increase agricultural yields is farmer groups. By forming a group it will be easier to achieve the desired goals compared to working alone. This study aims to identify the role of farmer group relationships in increasing the cocoa productivity of the Merta Abadi farmer group with its role as a learning class, a vehicle for cooperation, and a production unit. This research is located in Ekasari Village, Melaya District, Jembrana Regency, Bali. The research sample is the entire population or members of the Merta Abadi cocoa farmer group and uses a qualitative descriptive analysis method. Based on the research results, the role of farmer groups in increasing cocoa productivity of the Merta Abadi farmer group is in the “Very Good” category. Based on the results of the chi-square test with a significance level of 0.1 or 10%, there is no significant relationship between the role of farmer groups in increasing the cocoa productivity of the Merta Abadi farmer group. The Merta Abadi farmer group is expected to be able to improve the facilitation function of farming and foster group collaboration with other parties. Farmer groups also need socialization for nearby farmers who have not yet joined farmer groups so that the number of members increases and it is hoped that this will help improve the welfare of farmers in Ekasari Village.